2013
DOI: 10.3389/fnins.2013.00210
|View full text |Cite
|
Sign up to set email alerts
|

Stress and serial adult metamorphosis: multiple roles for the stress axis in socially regulated sex change

Abstract: Socially regulated sex change in teleost fishes is a striking example of social status information regulating biological function in the service of reproductive success. The establishment of social dominance in sex changing species is translated into a cascade of changes in behavior, physiology, neuroendocrine function, and morphology that transforms a female into a male, or vice versa. The hypothalamic-pituitary-interrenal axis (HPI, homologous to HP-adrenal axis in mammals and birds) has been hypothesized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 90 publications
(139 reference statements)
8
41
0
Order By: Relevance
“…Research on gonochoristic pejerrey has also come into conflict with the Substrate Competition for Enzymes hypothesis, since results on pejerrey larvae showed that the cortisol treatment was associated with significant increases in 11KT, but not T, during the first 4 weeks (Hattori et al 2009). In combination with data from Frisch et al (2007), an increase in cortisol levels was proposed as part of the trigger initiating sex change in sequential hermaphrodites by Solomon-Lane et al (2013), who argued that this elevation would increase corticotropinreleasing factor (CRF) signaling and activity of HPI axis. Their work on the bidirectional hermaphrodite Lythrypnus dalli (bluebanded goby) showed that cortisol peaked in early stages of sex change during which differences in HPI axis activity were also shown to reflect social status (Solomon-Lane et al 2013).…”
Section: Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on gonochoristic pejerrey has also come into conflict with the Substrate Competition for Enzymes hypothesis, since results on pejerrey larvae showed that the cortisol treatment was associated with significant increases in 11KT, but not T, during the first 4 weeks (Hattori et al 2009). In combination with data from Frisch et al (2007), an increase in cortisol levels was proposed as part of the trigger initiating sex change in sequential hermaphrodites by Solomon-Lane et al (2013), who argued that this elevation would increase corticotropinreleasing factor (CRF) signaling and activity of HPI axis. Their work on the bidirectional hermaphrodite Lythrypnus dalli (bluebanded goby) showed that cortisol peaked in early stages of sex change during which differences in HPI axis activity were also shown to reflect social status (Solomon-Lane et al 2013).…”
Section: Speciesmentioning
confidence: 99%
“…In combination with data from Frisch et al (2007), an increase in cortisol levels was proposed as part of the trigger initiating sex change in sequential hermaphrodites by Solomon-Lane et al (2013), who argued that this elevation would increase corticotropinreleasing factor (CRF) signaling and activity of HPI axis. Their work on the bidirectional hermaphrodite Lythrypnus dalli (bluebanded goby) showed that cortisol peaked in early stages of sex change during which differences in HPI axis activity were also shown to reflect social status (Solomon-Lane et al 2013). Most recently, long-term cortisol administration was shown to induce sex change in protogynous three-spot wrasse (Halichoeres trimaculatus; Nozu & Nakamura 2015).…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ). That these factors apparently also mediate agonistic behaviour and social status information implicates the HPI axis in linking social status to sex change in sequential hermaphrodites [Solomon-Lane et al, 2013].…”
Section: Sex Change and The Stress Responsementioning
confidence: 99%
“…The stress response, regulated through the hypothalamic-pituitary-interrenal (HPI) axis, modulates processes central to major life-history transitions, including changes in behaviour, metabolism, and growth [Wada, 2008;Solomon-Lane et al, 2013]. Through the actions of corticotropic releasing hormone (CRH) and glucocorticoid steroids (GCs), the HPI axis responds to environmental stressors, with potentially significant effects on gonadal fate ( fig.…”
Section: Sex Change and The Stress Responsementioning
confidence: 99%